Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10530-009-9645-7
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent pattern and process: the distribution and competitive dynamics of an invasive grass, Brachypodium sylvaticum

Abstract: Brachypodium sylvaticum, or false brome, a recent invader of North America, has spread rapidly following establishment in Oregon in 1939 and is now colonizing at least five US states. To understand how ecological processes and environmental context interact to facilitate invasion, we combined a GIS analysis of spatial patterns of invasion with a greenhouse competition experiment under two light and two nutrient levels, and a field competition-removal experiment. Brachypodium sylvaticum was concentrated along h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It is listed as a quarantined, invasive species in California, Washington, and Oregon, United States and has also been sighted in low abundance at several locations on the east coast of North America (Roy et al, 2011). It forms dense monocultures, typically under forest canopies, leading to a decrease in understory community diversity and an alteration in forest fire dynamics, which may prevent the establishment of tree seedlings (Holmes et al, 2010; Roy et al, 2011). Slender false brome is ideal for use in this study because its performance and competitive ability has been found to be influenced by mycorrhizal colonization (C. Lee, Portland State University, personal communication; R. Workman, unpublished data).…”
mentioning
confidence: 99%
“…It is listed as a quarantined, invasive species in California, Washington, and Oregon, United States and has also been sighted in low abundance at several locations on the east coast of North America (Roy et al, 2011). It forms dense monocultures, typically under forest canopies, leading to a decrease in understory community diversity and an alteration in forest fire dynamics, which may prevent the establishment of tree seedlings (Holmes et al, 2010; Roy et al, 2011). Slender false brome is ideal for use in this study because its performance and competitive ability has been found to be influenced by mycorrhizal colonization (C. Lee, Portland State University, personal communication; R. Workman, unpublished data).…”
mentioning
confidence: 99%
“…The combination of B. sylvaticum's shade tolerance, germination, and survival success in coniferous forests, and its high competitive ability under shade and high-nitrogen conditions (Holmes et al 2010), make it a formidable invader in the Pacific Northwest bioregion, where coniferous forests dominate the landscape. Especially once it has established, its high fecundity may ensure that heavy propagule pressure will further drive the population growth and spread of this invasive species (Roy et al 2011).…”
mentioning
confidence: 99%
“…For example, increased light availability can reduce SI (Schoch et al ., ). Light availability varies across the invasive range of B. sylvaticum and can affect outcomes of competitive interactions with native species (Holmes et al ., ). Results contrary to predictions of adaptation to drought stress may also be the result of functional trade‐offs between traits that interact with nitrogen, soil water and light availability.…”
Section: Discussionmentioning
confidence: 97%